2012
DOI: 10.1590/s1517-83822012000300022
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of canine parvovirus type 2c (CPV-2c) from symptomatic puppies

Abstract: Canine parvovirus type 2 (CPV-2) is a leading cause of diarrhea in puppies in several parts of the world. In this study CPV-2 was detected and recovered from puppies showing clinical disease from Montevideo, Uruguay. Samples were processed and used to infect CRFK and MDCK cells in order to isolate the virus.Out of twelve, two samples were positive for CPV-2. A genomic region of 583 bp was amplified and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
(6 reference statements)
0
6
0
3
Order By: Relevance
“…Across all RNA species, RNA-seq has revolutionized and become a widely used approach to study quantitative aspects of transcriptome profiling in the virus-infected cells Sun et al, 2014Sun et al, , 2019Zhou et al, 2017). In the current study, we have explored the miRNA milieu in CRFK cells infected with CPV-2c Laotian isolates (Puentes et al, 2012). We have identified 515 DEGs using sRNA libraries in either uninfected control or CPV-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Across all RNA species, RNA-seq has revolutionized and become a widely used approach to study quantitative aspects of transcriptome profiling in the virus-infected cells Sun et al, 2014Sun et al, , 2019Zhou et al, 2017). In the current study, we have explored the miRNA milieu in CRFK cells infected with CPV-2c Laotian isolates (Puentes et al, 2012). We have identified 515 DEGs using sRNA libraries in either uninfected control or CPV-infection.…”
Section: Discussionmentioning
confidence: 99%
“…La parvovirosis canina es una enfermedad causada por el virus del parvovirus canino, el cual se caracteriza por presentar principalmente un cuadro gastroentérico en cachorros, pudiendo llegar a causar la muerte (Duque et al, 2017). Actualmente, en las clínicas veterinarias es usual el diagnóstico de la enfermedad en base a los signos clínicos y condiciones de animal; sin embargo, este diagnóstico no es definitivo para su determinación (Puentes et al, 2012).…”
Section: Discussionunclassified
“…Some authors have suggested an update of the virus strains in current vaccines, taking into account the existing partial protection (Truyen 2006). Because of this, the isolation of new CPV circulating variants is important in order to be used in vaccine manufactures more effective from an immunogenic point of view (Puentes et al 2012). …”
Section: Discussionmentioning
confidence: 99%